On Certain Quadruple Fixed Points of Integral Type Contraction Mappings in G-Metric Spaces and its Applications (Journal of Scientific Research, 2022)
In this paper, the existence of common quadruple fixed point results for integral type contraction of two mappings in G-metric spaces is established. Some interesting consequences of our results are achieved. Moreover, we give an illustration that presents the applicability of the achieved results.